"Conflict and diplomacy: US and the birth of Bangladesh, Pakistan divides" - "Singh, Jaswant" (New Delhi, 2008)
The authors, Jaswant Singh and Maj. S.P. Bhatia, lead the readers along this twisted and torturous path of the birth of Bangladesh under Indian midwifery, intrigued by West Pakistani and the US diplomacy. The declassified US documents provide revealingly informative aspects of the US diplomacy during this challenging period.